2001
DOI: 10.1039/b108249c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sampling methods for 1,6-hexamethylene diisocyanate, (HDI) in a commercial spray box

Abstract: In this study three different types of samplers for the determination of 1,6-hexamethylene diisocyanate in air were compared. The experimental set up was a simulation of real life conditions with spray painting operations performed inside a commercial, full sized, spray box. The sampling methods were 1-(2-methoxyphenyl)-piperazine impregnated on glass fibre filter, and the same reagent in impinger, and also dibutylamine in impinger. All analyses were performed by LC-MS-MS. The determined concentrations varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The resulted product was quickly washed with DMF by centrifugation. The washing process was repeated for four times to ensure complete removal of the residue reagents (Ekman et al. 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulted product was quickly washed with DMF by centrifugation. The washing process was repeated for four times to ensure complete removal of the residue reagents (Ekman et al. 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The resulted product was quickly washed with DMF by centrifugation. The washing process was repeated for four times to ensure complete removal of the residue reagents (Ekman et al 2002). Excess EPs (1 g) were then added, and the mixture was kept in shaking incubator (N-Biotek, GyeongGi-Do, Korea) at 37°C overnight to ensure the full conversion.…”
Section: Eps Immobilization On Mwnt-cooh Via Hdismentioning
confidence: 99%
“…(19,22,24,27) Under a simulated spray painting environment, Ekman et al (24) observed no significant difference (α = 0.05) in the performance of closed-face single-stage filter sampler and an impinger when the same derivatizing agent (MPP) was used to quantify HDI monomer. However, we observed a significant difference between the closed-face single-stage filter samplers and impingers containing the same derivatizing agent.…”
Section: Table III Geometric Mean (Gm) Air Levels Of Monomeric and Pmentioning
confidence: 97%
“…Several studies (11,12,18,19,(22)(23)(24)(25)(26)(27)(28) have been performed to evaluate and compare some of these sampler types. However, the evidence is inconclusive regarding the suitability and accuracy of these methods for monitoring isocyanate exposure in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…Early methods were based on colorimetric techniques with restricted selectivity and sensitivity [6], while modern analytical approaches focus on derivatization with nucleophilic reagents, followed by liquid chromatographic (LC) separation and photometric or fluorometric detection. In the past decades, compounds containing amine functionalities, such as 1-(2-methoxyphenyl)-piperazine (2-MP) [7][8][9][10][11][12], 9-(N-methylaminomethyl)-anthracene (MAMA) [13,14], 1-(9-anthracenyl-methyl)-piperazine (MAP) [15,16], 1-(2-pyridyl)-piperazine (2-PP) [17], and 4-nitro-7-piperazino-benzo-2-oxa-1,3-diazole (NBDPZ) [18] were introduced as derivatizing reagents. In recent years, the use of mass spectrometry as a detection technique became more and more important because of its high selectivity and low limits of detection.…”
mentioning
confidence: 99%